THE EFFECT OF WORK HAPPINESS AND PSYCHOLOGICAL WORKLOAD ON ORGANIZATIONAL COMMITMENT WITH JOB EMBEDDEDNESS AS A MEDIATING VARIABLE AT PT. MIDTOU ARYACOM FUTURES, BANDAR LAMPUNG WORKING AREA - Nazwa Noor Nissa; Febrianty; Ayu Nursari (International Journal of Multidisciplinary Reseach, 2026)
This study aims to analyze the effect of Work Happiness and Psychological Workload on Organizational Commitment, with Job Embeddedness as a mediating variable among employees of PT. Midtou Aryacom Futures in the Bandar Lampung working area. This research employs a quantitative approach using a survey method through the distribution of questionnaires to employees, which are then analyzed using the SEM-PLS method. The results show that Work Happiness has a positive and significant effect on Organizational Commitment and Job Embeddedness, while Psychological Workload has a significant effect on Organizational Commitment but does not have a significant effect on Job Embeddedness. Furthermore, Job Embeddedness has a significant effect on Organizational Commitment and is proven to mediate the relationship between Psychological Workload and Organizational Commitment, but does not mediate the relationship between Work Happiness and Organizational Commitment. These findings indicate that work happiness, effective management of psychological workload, and employee embeddedness are important factors in enhancing employee commitment and loyalty within the organization.